FAKTOR PENDORONG KETERPILIHAN CALON LEGISLATIF PEREMPUAN DI PEMILIHAN UMUM DPRD KABUPATEN KUDUS 2014 - noviya nailul miskiyah; fitriyah .; puji astuti (Journal of Politic and Government Studies, 2016)
This research’s purpose is to identify driving factors of the election of three women candidates in DPRD at the Election of Parliament in Kudus Regency 2014. What makes the three women candidates can be selected from the many women candidates contesting Kudus Regency 2014. The type of research is qualitative descriptive. Depth interview method was used to collect the data toward all the women members of local legislative in Kudus Regency by the result of the Election 2014. Data reduction, data presentation, data conclusion and verification were used for the data processing method. The result of the research affords driving factors of the election of three candidates from the determinant factors: they dominate political asset which facilitate them to develop the network between political elites or to develop their own network, becomes a nomination at the insignificant serial number and strategic region’s election, obtain the supports from people’s trust toward the candidates for the social asset, economics asset to fund the legislative’s nomination, the best selection of the effective strategic issues as a way to convince the voters and incumbent popularity rate to bring up the credibility.Keywords: Driving Factors, Women Candidate, Elected